BENEFITS AND LIMITATIONS OF THE FLIPPED CLASSROOM APPROACH ACROSS DIFFERENT PROFICIENCY LEVELS - Kholbutayeva Shakhnoza (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study examines the applicability and effectiveness of the flipped classroom methodology in different learning contexts, with particular emphasis on students’ language proficiency levels and readiness for autonomous learning. While the flipped classroom approach has gained significant recognition for promoting learner-centered education and active engagement, its implementation may not be equally effective across all learner groups. This research is based on a case study conducted at Uzbekistan State World Languages University among beginner-level students learning Chinese as a second foreign language. Due to the linguistic complexity of Chinese, including its logographic writing system, tonal pronunciation, and extensive memorization requirements, students faced challenges in independently engaging with pre-class materials. The flipped classroom model proved more effective in English language classes, where students demonstrated intermediate to advanced proficiency levels (B2–C1) and were capable of autonomous learning. The findings indicate that while the flipped approach enhances critical thinking, engagement, and practical application of knowledge, its success largely depends on learners’ prior knowledge, language competence, and self-directed learning skills. The study highlights the importance of adapting teaching methodologies to specific educational contexts and suggests that traditional, teacher-centered approaches remain more suitable for beginner-level learners in complex linguistic environments.